Mucous layer effects towards nasal airflow - Chih, Fang Lee; Kamarul Arifin, Ahmad, Dr.; Rushdan, Ismail, Dr.; Suzina, Sheikh Abdul Hamid, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/